2016
DOI: 10.1002/adma.201603808
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Benzoquinone Additive for Efficient and Stable Planar Perovskite Solar Cells

Abstract: Device stability of planar perovskite solar cells is improved by virtue of multifunctional BQ additive. The morphology and crystal quality of the perovskite films are improved because BQ slows the rate of perovskite crystal formation. Electron transfer from perovskite to BQ reduces charge-recombination losses, and the oxidizing ability of BQ effectively suppresses the formation of metallic lead and improves device lifetime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 41 publications
4
116
0
Order By: Relevance
“…As shown in Figure b, the peak near 8.78 ppm for the FAI solution w TPFPB additive is also split into two peaks similar to the splitting observed in the perovskite solution w TPFPB. The splitting of FA + protons into two new signals has also been observed by other research groups and us, and it is ascribed to the strong interaction between amino group (—NH 2 ) and TPFPB, as confirmed by very early reports . To further confirm the existence of F—H hydrogen bonds between TPFPB and FAI, we also measured the 19 F NMR spectra of TPFPB and TPFPB+FAI in the DMSO solution (Figure c).…”
Section: Resultssupporting
confidence: 83%
“…As shown in Figure b, the peak near 8.78 ppm for the FAI solution w TPFPB additive is also split into two peaks similar to the splitting observed in the perovskite solution w TPFPB. The splitting of FA + protons into two new signals has also been observed by other research groups and us, and it is ascribed to the strong interaction between amino group (—NH 2 ) and TPFPB, as confirmed by very early reports . To further confirm the existence of F—H hydrogen bonds between TPFPB and FAI, we also measured the 19 F NMR spectra of TPFPB and TPFPB+FAI in the DMSO solution (Figure c).…”
Section: Resultssupporting
confidence: 83%
“…[14] By decreasing the concentration of the lead ion species used during perovskite film formation, the concentration of defect precursor could be reduced in solutions. [15] By virtue of the weak reduction properties of a benzoquinone additive, we were able to suppress the formation of metallic lead and effectively extend the lifetime of the PSCs. [12] Through systematic experimental studies, we showed that Frenkel defects are detrimental to the stability of PSCs and that metallic lead related vacancies are a possible intrinsic origin of carrier traps.…”
Section: Doi: 101002/advs201801079mentioning
confidence: 99%
“…[11,12,15] Since this phase-transition temperature is much lower than the operating temperature of PSCs in naturally occurring terrestrial environments, the influence of the low-temperature phase transition on device performance should be negligible. [11,12,15] Since this phase-transition temperature is much lower than the operating temperature of PSCs in naturally occurring terrestrial environments, the influence of the low-temperature phase transition on device performance should be negligible.…”
Section: Doi: 101002/advs201801079mentioning
confidence: 99%
“…However, the perovskite films consisting of polycrystalline micro–nanograins are usually prepared by the solution processing methods, which inevitably introduce many defects into the grain boundaries and surface of perovskite films. In addition, due to the low thermal stability of CH 3 NH 3 PbI 3 , thermal annealing (typically ≈100 °C) can cause nonstoichiometry in composition, and also decompose CH 3 NH 3 PbI 3 to PbI 2 on the surface and at the grain boundaries of polycrystalline films, where the unsaturated or undercoordinated Pb ions are most frequently found . Although a certain content of PbI 2 distributed into the perovskite layers and grain boundaries result in the reduced hysteresis and ionic migration, the uncontrollable formation and unpredictable location of PbI 2 also lead to the wide variance in terms of photovoltaic performance, reproducibility, and device stability .…”
Section: Introductionmentioning
confidence: 99%